The impact of rational emotive behavior therapy approach with Islamic values on children with sexual abuse trauma - Zuliani, Hetti; Kee, Pau; Sapeer, Noor (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2024)
This study aims to evaluate the effectiveness of Rational Emotive Behavior Therapy integrated with Islamic values (REBT-NIS) in reducing trauma symptoms in children who have experienced sexual abuse in Aceh. This approach combines REBT techniques with Islamic values such as ridha (contentment), patience, and ikhlas (sincerity), which are expected to help children develop more rational and positive thinking in overcoming their trauma. The study used a quasi-experimental design with pre-test and post-test assessments to measure trauma, anxiety, depression, and stress symptoms in the children involved. The results showed a 50% reduction in trauma symptoms after the implementation of REBT-NIS, with significant improvements in all trauma dimensions measured using the Child PTSD Symptom Scale (CPSS) and Depression, Anxiety, and Stress Scale (DASS). These findings indicate that the REBT-NIS approach, which integrates Islamic values, is effective in supporting trauma recovery in sexually abused children, particularly in Aceh. This approach contributes to trauma therapy theory and practice by demonstrating the importance of integrating religious values into evidence-based psychological therapy.